Endometriosis in the rectum accompanied by hemorrhoids leading to diagnostic pitfalls: a rare case report - Xiuying Shi; Chuifeng Fan (BMC, 2018)
Abstract Background Hemorrhoid is a common anorectal disease. Hemorrhoids accompanied by endometriosis are unusual. As endometriosis in the rectum may mimic many other diseases, including cancer and inflammation, its diagnosis may be difficult, especially when it is combined with other diseases. Case presentation Here, we present a rare case of a patient with hemorrhoids accompanied by endometriosis in the rectum. The endometriosis mass was detected by digital rectal examination and CT scan and confirmed by pathological examination. The mass was approximately 0.8 cm × 0.6 cm and located in the muscularis and submucosa of the rectum 8 cm from the anus. Conclusions In this case, hemorrhoid is a common disease of rectum and anal canal. However, when it is complicated by another rare disease, the rare one can be easily neglected because of the existence of the common one, especially when the two diseases have similar lesions or symptoms. We suggest that strict physical examination, such as the digital rectal examination in the current case, is critical for correct disease diagnosis.